TECTONIC CONTROLS ON THE DEVELOPMENT OF UNCONFORMITIES - THE NORTH SLOPE, ALASKA - Coakley, B; Watts, A (1991)
The geology of northern Alaska is defined by two complementary, synchronous tectonic events. Opening of the Canada basin breached the south facing Ellesmerian passive margin in the Late Jurassic, cutting off northerly derived sediment and initiating thermal subsidence of the north facing Beaufort passive margin. Uplift of the Brooks Range on thrust faults loaded the lithosphere, creating the Colville trough, a foreland basin more than 10 km deep, and providing the bulk of the sediments that filled it. The northerly advance of the Brooks Range caused the two independent loads to flexurally interfere. The Beaufort passive margin is separated from the foreland by the Barrow Arch, which is, in part, the flexural bulge due to the interaction of these two loading events. A record of this interaction is preserved in the sediments north and south of the Barrow Arch. This stratigraphy, coupled with simple basin modelling, has been used to consider the flexural and stratigraphic effects of the evolving thrust wedge and basin filling. -from Authors